SP1-mediated glycolytic reprogramming promotes tumorigenesis and progression in pancreatic cancer - Hang, Hexing; Yu, Mengyu; Zhu, Linxi; Tang, Neng; Fu, Xiao; Cai, Zhenghua; Yan, Minghao; Chen, Yi; Yang, Lei; Wu, Jianzhuang; Tang, Jiatong; Xie, Yu; et al. (Advanced science, 2025)
Pancreatic ductal adenocarcinoma (PDAC) is a highly lethal malignancy, commonly progressing from pancreatic intraepithelial neoplasia (PanIN). However, the molecular alterations in PanIN lesions and their contribution to PDAC progression remain poorly defined. Here, using laser capture microdissection-based proteomics of patient tissues, early metabolic remodeling and upregulation of the transcriptional factor specificity protein 1 (SP1) in PanIN lesions are identified, which persisted into the PDAC stage. That SP1 overexpression promoted PDAC proliferation is demonstrated in patient-derived organoid xenograft models (PDOXs), while deletion of Sp1 inhibited tumorigenesis and progression in a transgenic mouse model of PDAC (KrasLSL-G12D/+; Trp53LSL-R172H/+; Sp1LOXP/LOXP; Pdx1-Cre). ChIP-seq and isotope tracing revealed that SP1 enhances aerobic glycolysis by transcriptionally activating 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase (PFKFB4), a key regulator of glycolysis. Combination therapy targeting SP1 and PFKFB4 demonstrated significant efficacy in PDAC models in vivo. The findings suggest that SP1 is a critical regulator of PDAC initiation and progression through its control of metabolic remodeling. Targeting SP1 and PFKFB4 represents a promising therapeutic strategy for PDAC treatment.
Zuerst veröffentlicht: 20. August 2025
Gesehen am 13.01.2026